Allotment gardens in the Lublin downtown in the spatial and urban planning context – origins and issues concerning their preservation - Przesmycka, Natalia; Strojny, Rafał (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
Allotment gardens situated in city centers are particularly at risk of the development of buildings serving commercial (service-related or residential) purposes. The present article presents allotment gardens in the downtown of Lublin from the historical, architectural and landscape context. The analysis of urban planning determinants was undertaken for the functioning of gardens from the moment of their establishment until the present day at the example of the oldest of them – “Nasza Zdobycz nad Bystrzycą”. The article also constitutes an attempt to explain the increasing alienation of the owners of allotment gardens, progressing devastation of the area of allotment gardens as well as to present a suggestion for design application inscribing in the scope of revitalization of this area.